Randomised double-blind trial of acyclovir (Zovirax) and adenine arabinoside in herpes simplex amoeboid corneal ulceration. Issue 11 (November 1985) - Collum, L M; Logan, P; McAuliffe-Curtin, D; Hung, S O; Patterson, A; Rees, P J
Abstract : Fifty-one patients were treated in a dual-centre, double-blind comparison of acyclovir and adenine arabinoside in herpetic amoeboid (geographic) corneal ulceration. Twenty-four of the 25 patients receiving acyclovir healed in a mean time of 12.2 days, while 24 of the 26 patients treated with adenine arabinoside healed in a mean time of 11.0 days. There was no statistically significant difference between the two groups in terms of healing. A second analysis, excluding any patients who had received antiviral treatment immediately prior to entry into the study, showed that 18 of the 19 who received acyclovir healed in an average of 11.7 days and 18 of the 19 recipients of adenine arabinoside healed in a mean time of 11.2 days. Again the difference was not statistically significant.